GraphCrypto: Next generation data security approach towards sustainable smart city building. (September 2021) - Mishra, Alekha Kumar; Puthal, Deepak; Tripathy, Asis Kumar
Highlights: An operation on graphs is defined that obeys the properties of an algebraic group. The proposed mechanism represents plaintext, ciphertext, and key as a graph. It provides an unambiguous mapping process from plaintext to graph and vice versa. Unlike other symmetric cryptosystems, the encryption and decryption keys are not the same. The decryption key graph is the inverse graph of the encryption key graph. Abstract: Data confidentiality and integrity are essential security goals in the data communication in the smart city or similar applications. Despite significant changes in modern data communication systems and devices, the cryptosystems are still the primary option to achieve data security. Several cryptosystems have been developed, implemented and standardized to date. However, there is always a continuous demand for a new cryptosystem for providing security during data communication. In this paper, a novel symmetric cryptosystem is presented for achieving data confidentiality. The proposed cryptosystem is a graph-based system, where an algebraic structure of directed graphs along with a novel operation is defined to provide the base of the cryptosystem. Here, a directed graph represents a plaintext, a ciphertext, and a secret key as well. The defined operation is used for encrypting and decrypting plaintext and ciphertext graphs. The proposed cryptosystem provides a simplified transformation process and representation of plaintext to plaintext graph. The correctness of the proposed cryptosystem is validated, and also shown that the conventional brute-force approach to obtain the key from either plaintext or ciphertext is exponential and this computational time is significantly higher than AES. This implies that the proposed cryptosystem is highly secured against this attack. The proposed cryptosystem is implemented and compared with AES and the results infer that it incurs a marginally higher execution time than the AES for larger plaintext due to the involvement of matrix operations.